Crystal structure of 3-methoxy-4-[2-(thiazol-2-yl)diazen-1-yl]aniline monohydrate - Nutchanikan Phiromphu; Kittipong Chainok; Apisit Songsasen; Tanwawan Duangthongyou (Acta Crystallographica Section E: Crystallographic Communications, 2019)
In the title hydrated azo dye, C10H10N4OS·H2O, the benzene and thiazole, are nearly coplanar, with a dihedral angle between their mean planes of 4.69 (17)°. The aromatic rings on the –N=N– moiety exhibit a trans configuration. The crystal structure features many types of intermolecular interactions involving all the functional groups – strong hydrogen bonds (N...H and O...H), weak hydrogen bonds (C—H...O and C—H...N), C—H...π and π–π interactions – resulting in the formation of a three-dimensional framework.